The effect of physical activity on the dynamics of myocardial bioelectrical activity in students - Nikiforova, O.N.; Markin, E.V.; Soparev, A.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to investigate the effect of the nature of physical activity on the dynamics of myocardial bioelectrical activity in students at an agricultural university. Methods and structure of the study. A total of 62 students from an agricultural university were examined, from whom two groups were identified based on their levels of physical activity: Group A comprised students who continued to practise selected sports (25 individuals), and Group B comprised students who had stopped practising sport after their third year (41 individuals). The study of myocardial bioelectrical activity in students at an agricultural university was carried out using the results of the standard method for interpreting electrocardiograms. All parameters were recorded three times at each stage of the study: at rest, after a graded physical exercise test, and during the recovery period. A two-stage ‘step test’ on a 40 cm high step, based on the method of Y.S. Weinbaum, was used as the submaximal graded exercise test. All data obtained from the functional study were analysed using the method of variational statistics. Results and conclusions. Resting ECG data indicated an improvement in cardiovascular function among students participating in selected sports compared with those who had stopped practising sport. This was reflected in a prolongation of the cardiac cycle by 35.7 beats per minute, and the presence of a high percentage of moderate (68%) and marked (32%) sinus arrhythmia, indicating an increase in cardiac functional reserves among students who engaged in physical exercise throughout their time at university. Informative indicators for assessing the bioelectrical activity of the students’ myocardium under different types of physical activity include: the severity of sinus arrhythmia (∆RR=0.25–0.50 s), the characteristics of RR intervals, QT intervals and the amplitudes of the Pıı, Rıı, Tıı waves and the total voltage of the R waves in standard electrocardiogram leads.